Advancing exposure data analytics and repositories as part of the European Exposure Science Strategy 2020–2030. (December 2022) - Kosnik, Marissa B.; Kephalopoulos, Stylianos; Muñoz, Amalia; Aurisano, Nicolò; Cusinato, Alberto; Dimitroulopoulou, Sani; Slobodnik, Jaroslav; De Mello, Jonathas; Zare Jeddi, Maryam; Cascio, Claudia; Ahrens, Andreas; Bruinen de Bruin, Yuri; et al.
Abstract: High-quality and comprehensive exposure-related data are critical for different decision contexts, including environmental and human health monitoring, and chemicals risk assessment and management. However, exposure-related data are currently scattered, frequently of unclear quality and structure, not readily accessible, and stored in various—partly overlapping—data repositories, leading to inefficient and ineffective data usage in Europe and globally. We propose strategic guidance for an integrated European exposure data production and management framework for use in science and policy, building on current and future data analysis and digitalization trends. We map the existing exposure data landscape to requirements for data analytics and repositories across European policies and regulations. We further identify needs and ways forward for improving data generation, sharing, and usage, and translate identified needs into an operational action plan for European and global advancement of exposure data for policies and regulations. Identified key areas of action are to develop consistent exposure data standards and terminology for data production and reporting, increase data transparency and availability, enhance data storage and related infrastructure, boost automation in data management, increase data integration, and advance tools for innovative data analysis. Improving and streamlining exposure data generation and uptake into science and policy is crucial for the European Chemicals Strategy for Sustainability and European Digital Strategy, in line with EU Data policies on data management and interoperability.